Primary Headaches In Transgender Men: A Pilot Study - Leite, Jardelina Brena Rocha; Arca, Vitor Maia; Diniz, Erik Trovão; Filho, Pedro Augusto Sampaio Rocha (Headache Medicine, 2023)
Full abstract in PDF.